Carbachol stimulates a different phospholipid metabolism than nerve growth factor and basic fibroblast growth factor in PC12 cells. - Pessin, M S (1991)
We have examined 1,2-diglycerides (DGs) generated in PC12 cells in response to the muscarinic agonist carbachol and compared them with those generated in response to the differentiation factors nerve growth factor and basic fibroblast growth factor. Whereas carbachol stimulates a greater release of inositol phosphates, all three agonists generate similar levels of DGs. In this report, we have analyzed the molecular species of PC12 DGs generated in response to these three agonists. Additionally, we have analyzed the molecular species of PC12 phospholipids. The data indicate that 1) after 1 min of either nerve growth factor or basic fibroblast growth factor stimulation, DGs arise primarily from phosphoinositide hydrolysis; 2) in contrast, after 1 min of carbachol stimulation, DG are generated equally by both phosphoinositide and phosphatidylcholine hydrolysis; and 3) after 15 min of stimulation by any of these agonists, DGs are generated largely by phosphatidylcholine hydrolysis, with a smaller component arising from the phosphoinositides. These results suggest that at least part of the mechanism by which PC12 cells distinguish between different agonists is via alterations in phospholipid sources and kinetics of DG generation.